Treatment Response, Survival Benefit and Safety Profile of PD-1 Inhibitor Plus Apatinib Versus Apatinib Monotherapy in Advanced Colorectal Cancer Patients - Pan, Dengdeng; Liu, Dongliang; Liang, Lichuan; Shen, Tongyi; Shi, Chenzhang; Qin, Huanlong (Frontiers in Oncology, 2022)
Purpose: Programmed cell death protein 1 (PD-1) inhibitor plus apatinib is reported to be a promising strategy for advanced cancers. Moreover, a PD-1 inhibitor or apatinib exerts a certain efficacy in advanced colorectal cancer (CRC), whereas their synergistic effect is unclear. This study aimed to evaluate the treatment efficacy and safety of a PD-1 inhibitor plus apatinib in advanced CRC patients. Methods: In total, 45 advanced CRC patients who received a PD-1 inhibitor plus apatinib (PD-1 inhibitor plus apatinib group, N=20) or apatinib monotherapy (apatinib group, N=25) as third-line therapies were enrolled in the current study. Results: The objective response rate (20.0% vs. 8.0%) (P=0.383) and disease control rate (70.0% vs. 52.0%) (P=0.221) were numerically increased in the PD-1 inhibitor plus apatinib group, respectively, compared with the apatinib group, but no statistical significance was observed. The median progression-free survival (PFS) was 7.5 versus 4.8 months; the 1-year PFS rate was 32.5% versus 9.9%; the median overall survival (OS) was 12.3 versus 8.7 months; and the 1-year OS rate was 50.7% versus 27.0% in the PD-1 inhibitor plus apatinib group versus the apatinib group, respectively. PFS (P=0.038) and OS (P=0.048) were prolonged in the PD-1 inhibitor plus apatinib group compared with the apatinib group. PD-1 inhibitor plus apatinib (versus apatinib) was independently associated with longer PFS (P=0.012) and OS (P=0.009). The majority of the adverse events were of grade 1-2, wherein the incidence was similar between groups, except for the fact that the incidence of capillary proliferation was elevated in the PD-1 inhibitor plus apatinib group compared with the apatinib group (25.5% versus 0.0%) (P=0.013). Conclusion: PD-1 inhibitor plus apatinib presents a potential improvement in efficacy and survival benefit compared with apatinib monotherapy, with tolerable safety in advanced CRC patients.